Action observation affects mental representation development of a complex motor - Cruz, A.; Jang, D.; Park, S. (International Journal of Sport Psychology, 2016)
This research investigated the effect of action observation-viewing a demonstration of a model-on the development of the mental representation of a complex motor skill. Eighty participants were categorized based on their level of expertise in tae kwon do and then divided into action observation and control groups. Participants' mental representation structures of the roundhouse kick were measured using the structural dimensional analysis-motoric method. Hierarchical cluster analyses revealed changes between pretest and posttest, and between pretest and delayed posttest in terms of cognitive structures that were functionally and biomechanically organized within the experimental group participants with less tae kwon do experience. No significant differences were observed in the cognitive structures of the more experienced experimental group participants. This experiment is the first to show that action observation can be mental representation of a complex skill over the course of learning.a powerful tool for acquiring and improving the mental representation of a complex skill over the course of learning.